Diversity of shrews in Ethiopia, with the description of two new species of Crocidura (Mammalia: Lipotyphla: Soricidae) - Lavrenchenko, Leonid A.; Voyta, Leonid L.; Hutterer, Rainer (Zootaxa, 2016)
Two new species of white-toothed shrews, Crocidura afeworkbekelei and Crocidura yaldeni, are described from southern Ethiopia. Comparisons are made with other species of Crocidura known to occur in Ethiopia. A list of 28 species of shrews known from Ethiopia is provided, 10 of which (including both newly described species) are currently considered to be endemic to Ethiopia. The endemic shrew fauna consists of forest and montane species known to occur within the altitudinal range of 1200–4050 m a.s.l. The remarkable number of endemic species of Crocidura shows that the Ethiopian Plateau is an important centre of diversity and adaptive radiation of the genus. Current cytogenetic and molecular data support the monophyly of most species of Crocidura endemic to Ethiopia.